FDG PET/CT in Patient with Brain Metastasis from Cervical Carcinoma: A Case Report - Pusuwan, Pawana; Chansilpa, Yaowalak; Chawalparit, Orasa (The ASEAN Journal of Radiology, 2023)
Central nervous system involvement by cervical cancer is uncommon. We report a rare case of cerebral metastasis from cervical carcinoma which was demonstrated on FDG PET/CT. The prior routine MRI brain study showed no evidence of metastasis. Apart from cerebral metastasis, PET/CT also showed multiple sub-centimeter hypermetabolic nodules in both lungs with metastatic nodes involving the right hilar and sub-carinal region. Whole body PET/CT may be helpful not only to localize the lesion in the brain but also to demonstrate other unsuspected metastatic lesions.